COLLECTION OF FAGOPYRUM MILL WORLD GENEPOOL: FORMATION, STUDING AND USE OF THE SAMPLES - Коруняк, О. П.; Бурдига, В. М.; Рарок, А. В.; Рарок, В. А. (Podilian Bulletin: Agriculture, Engineering, Economics, 2017)
The article presents the methodology and results of collection formation and studying of samples of buckwheat in the Research Institute of cereals after. A. Alekseeva. Today the collection gene pool of State agrarian and engineering university in Podilya includes all categories of genetic resources; which belong to thirteen species of Fagopyrum family: local varieties-population; hybrid populations; breeding varieties of conventional and intensive types; wild species; botanical forms; poliployidy; genetic markers; mutants. The collection includes about 1;000 samples collected from different regions of the former Soviet Union and 14 countries. The most voluminous the common species of buckwheat is presented in collection (283 samples): the local population varieties and forms from various regions of Ukraine; Russia; Belarus and the countries of far and near abroad (China; Japan; India; France; Poland; Lithuania and Latvia). Also there was presented breeding varieties-population – 137 samples: domestic breeding – 46; selection of Russia – 35; Belarus – 30; foreign countries – 26 samples. Because the polymorphism of Common buckwheat (Fagopyrum esculentum Moench.) is rather narrow; in their collection the mutants are very valuable both for breeding and for the related sciences. of 381 model. The collection includes 381 such samples. Appreciating the elements of productivity and other characteristics of mutants evaluation we identify a number of valuable forms. It was found a number of sources of high productivity and resistance to extreme growing conditions. Selected samples will be included into the breeding program and will serve as parent forms to create new varieties of buckwheat.